Bibliografia na Śląsku, Śląsk w bibliografii (PDF 1,59 MB) (Książnica Śląska, 2025)
The main topic of the text are bibliographic works carried out bythe Silesian Library and its predecessors (the Library of the SilesianParliament and the Public Library of Silesia). The author traced thehistory of these activities from the pre-war years to the present day.She described the creation of Silesian retrospective and current bibliographies. In the article are presented the changes that occurred incollecting, selecting and recording bibliographic material. It is alsodiscussed the current state of bibliographic work carried out withinthe Silesian Collections Department of the Silesian Library.